Investigating the influence of individually espoused cultural values on teachers' intentions to use educational technologies in Chinese universities. Issue 5 (18th August 2019) - Teo, Timothy; Huang, Fang
ABSTRACT: This study used the technology acceptance model to examine the influence of individually espoused cultural values on teachers' intentions to use technology in Chinese universities. To address the limitations of model parsimony, the lack of studies in developing countries and the cultural biases in the technology acceptance literature, this study was conducted in a developing country – China. It extended the constructs of subjective norms and facilitating conditions into the technology acceptance model and investigated the influence of individually espoused cultural values on technology acceptance. The four cultural value dimensions, including masculinity versus femininity, individualism versus collectivism, uncertainty avoidance, and long-term versus short-term orientation, were measured at the individual level, as technology acceptance was considered an individual concern. To test the hypothesised model, data from 502 teachers in Chinese universities were analysed using structural equation modelling. The results revealed that technology acceptance model was a valid framework for explaining Chinese teachers' technology acceptance. Perceived usefulness, subjective norms, attitudes towards use and culture were all significant determinants of behavioural intentions, with attitudes towards use having the largest effect. This study demonstrated the significant influence of subjective norms on perceived usefulness. Specifically, it showed that they facilitated the influence of perceived ease of use and perceived usefulness on attitudes toward use.